(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2018)
National Archives of Georgia preserves the document (Fund 284, registered 1, description 597, case administration and widespread speaking languages, 1926-1927, p. 98-108), which describes Georgian administrative units of 1926-1927 according to case administration and widespread speaking languages (the document is written in Russian). In mentioned archival material the Georgian SSR is divided into 26 districts and 519 administrative units. In the Georgian SSR of 1926-27 years Georgian was used as language of the case administration in 395 administrative units, Russian – in 92, Armenian - in 8 and Turkish – in 6. In different districts case administration was monolingual, bilingual, trilingual and quadrilingual. According to the mentioned source 418 monolingual communities are described in total, among them Georgian – 367, Abkhaz – 18, Turkish – 11, Armenian – 9, Ossetian – 6, Russian– 6 and Greek – 1. Thus, after the Georgian state language, most of all, Russian was used as the language of case administration. According to the administrative unites speaking languages were monolingual – 418, bilingual – 75, trilingual – 16, quadrilingual – 7, There are registered 98 communities in total. As we can see, on the territory of Georgia, mostly, the Georgian state language was used ascase-administration and speaking language. After Georgian, Russian was used most of all. However, there is inappropriate correspondence between indexes of the use Russian as case administration (92) and speaking language (20). In particular, according to the archival material it is clear that the mentioned language had the function as an official language in different structures and the people speaking in that language were much less. This again proves the necessity of the use of Russian as the language of case administration based on language standards and regulations developed by the heads of the Soviet Union. In contrast, despite the language policy created artificially, Russian as a widespread speaking language was less commonly used in Georgian.